Breastfeeding and women living with HIV: Is it possible to move beyond the avoidance? - Annunziata Carlea; Laura Letizia Mazzarelli; Laura Sarno; Caterina Fulgione; Dalila Mantelli; Maurizio Guida (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2022)
The risk of mother-to-infant transmission of HIV 1 during breastfeeding ranges from 10% to 15% in the absence of maternal Antiretroviral Therapy (ART) and infant Antiretroviral (ARV) prophylaxis. WHO guidelines 2016 recommend women living with HIV and fully supported for ART adherence should breastfeed for at least 12 months and up to 24 months or longer. Anyway, in high-income settings, women living with HIV are suggested to avoid breastfeeding, regardless of maternal viral load or antiretroviral therapy status. The advantages of breastfeeding in low and middle-income settings are well recognized. This brief narrative review aims to summarize existing evidence on mechanisms and risk factors for HIV transmission during breastfeeding and the possible prevention strategies in the context of ART adherence.